ESPAÇO ESPIADO: O USO DE CRACK INSTITUINDO ESPACIALIDADES VIVENCIADAS POR ADOLESCENTES DO SEXO MASCULINO EM PONTA GROSSA – PARANÁ - Rocha, Heder Leandro (2013)
The objective of this research is to understand the institution spatialities related to use of crack by adolescent boys residents of the outskirts of Ponta Grossa - Paraná. Your practices are linked to drug use, theft, and violence in conflicts with other groups empowers negative social representations which focus on their bodies, considered as deviants. Teenagers „addicts‟ and „patients‟ need correction / treatment by the state apparatuses and institutions are directed to as the Therapeutic Community Treatment Marcos Fernandes Pinheiro, one that receives children and adolescent boys in the city of Ponta Grossa - Paraná. The identity elements constituting these guys, like age, gender, race and social class they are experienced in everyday defended and interrelations constituting their spatial practices. The first step in mapping these relationships has been the realization of six in-depth interviews using a semistructured script, it often was not followed because the circumstances of the interview. The interviews totaled approximately nine hours of audio and dozens of pages to transcription directly. Talks were organized into categories and discursive systematized from a database, totaling 397 evocations organized into two main axes. The first brings a direct reference of space evidencing spatialities that make up the daily life of the boys, already the second is composed of those who did not have a direct reference to a space, as dealt with representations divided in past, present and future. The treatment is assumed as a mark in their lives, such as before and after. But, the challenges are imposed by spatialities when the return to old homes. Giving voice to these guys sometimes criminalized, invisible and commonly misunderstood is to show there are other readings of reality, that there are other possible geographies. Guys, who beyond of a position of victim are active in their spatial practices and choices, enter to drug trafficking; for example, can be a search for respect or economic support. The very conceptualization of space / spatiality is tensioned by the practices of boys investigated and the idea of "space spied" is elaborated (corporeality arising from the use of crack) to give the phenomenon intelligible object of this research. The spatial experiences of adolescents users of crack are connected to multiple spatialities that converge in different temporalities, their positions in the face of different power configurations are fluid and locational they move between margin and center positions, the economy live more or less scheduled.